PWA (Progressive Web Apps)-Based PWA-Based Mobile Service Application Development - Moh Anshori Aris Widya; Nur Wakhidah (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
In the rapid development of science and technology, people are encouraged to use computers. Computers are one of the human tools used for data processing, both in government agencies, education, health, private and other businesses. Currently information is needed, with the need for information, a data processing system using a computer is applied to make it easier for users to perform computerized data processing. The existence of Integrated Service Posts (Posyandu) in Indonesia is now almost evenly distributed to the village level and even RT / RW. This proves that the role and care of the community in health services is very important, and is not only the responsibility of the government.